Physicochemical Characterization Of Lactose-based Ester As Potential Pharmaceutical Biosurfactant - U. H. Zaidan; M. B. Abdul Rahman; A. B. Salleh; M. Basri; S. S. Othman (International Journal of Pharmaceutical Sciences Research, 2024)
Non-Indexed Publication